2017
DOI: 10.1021/acssuschemeng.6b03194
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extraction of Cellulose Nanocrystals through Hydrochloric Acid Hydrolysis Catalyzed by Inorganic Chlorides under Hydrothermal Conditions

Abstract: Four inorganic chlorides were introduced into hydrochloric acid hydrolysis to extract cellulose nanocrystals (CNCs) from microcrystalline celluloses (MCC) under hydrothermal conditions. The as-prepared CNCs were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared (FT–IR), and thermogravimetric analysis (TGA). The role of inorganic chlorides including ferric chloride hexahydrate (FeCl3·6H2O), copper chloride dihydrate (CuCl2·2H2O), aluminum chloride (AlCl3), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 41 publications
3
69
0
4
Order By: Relevance
“…This is due to the lack of an electrostatic repulsion charge between crystal particles because chlorite ions are easily removed during the dialysis process[Lima and Borsali 2004;Roman and Winter 2004;Wang et al 2007]. In addition, NCC particles hydrolyzed by HCl have a strong hydrogen bonding at the surface of NCC particles resulting in agglomeration[Cheng et al 2017]. Similar observations were also reported by previous researchers[Corrêa et al 2010] where NCCs particles hydrolyzed with hydrochloric acid was in agglomeration.…”
supporting
confidence: 69%
“…This is due to the lack of an electrostatic repulsion charge between crystal particles because chlorite ions are easily removed during the dialysis process[Lima and Borsali 2004;Roman and Winter 2004;Wang et al 2007]. In addition, NCC particles hydrolyzed by HCl have a strong hydrogen bonding at the surface of NCC particles resulting in agglomeration[Cheng et al 2017]. Similar observations were also reported by previous researchers[Corrêa et al 2010] where NCCs particles hydrolyzed with hydrochloric acid was in agglomeration.…”
supporting
confidence: 69%
“…The crystallinity index was 86.5% ± 0.3% and the maximum thermal decomposition temperature was 344 ∘ C. The hydrolysis system of Cr(NO 3 ) 3 -H 2 SO 4 was also investigated by Chen and coworkers [127]. In this work, the maximum yield and highest crystallinity of CNCs were obtained under hydrolysis conditions of 0.22 M Cr(NO 3 ) 3 , 0.80 M H 2 SO 4 , and 82.2 ∘ C within 1 h. Other transition metals were examined as well for catalyzing the hydrolysis of raw cellulose materials to prepare CNCs, such as Fe(III), Al(III), Ni(II), Co(II), and Mn(II) [68,128,129], and they will not be elaborated in detail.…”
Section: Other Methods Some New Methods For the Preparation Of Cncs mentioning
confidence: 99%
“…Cheng et al reported an inorganic chloride/hydrochloric acid system for extracting CNCs from microcrystalline cellulose (MCC) under hydrothermal conditions [68]. Four inorganic chlorides including FeCl 3 ⋅6H 2 O, CuCl 2 ⋅2H 2 O, AlCl 3 , and MnCl 2 ⋅4H 2 O were investigated in this work.…”
Section: Mineral Acid Hydrolysismentioning
confidence: 99%
“…Therefore, in order to increase the economic value of sugarcane bagasse, in this work we used cellulose isolated from sugarcane bagasse as a filler of chitosan polymer. Some methods to obtain pure cellulose from a materials has been developed, including chemical [4], mechanical [5], and biological [6] methods. This research employed chemical extraction method, which was acid hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…This research employed chemical extraction method, which was acid hydrolysis. Cellulose extraction through hydrolysis with strong acid is the most common used method [2,4]. This process include the hydrolysis of the amorphous parts of cellulose and hemicellulose fibers [7,8].…”
Section: Introductionmentioning
confidence: 99%